Efeito protetor do 1,8 cineol na pancreatite aguda induzida por ceruleína em camundongos - Lima, Patricia Rodrigues (2013)
Acute pancreatitis (AP) is an inflammatory condition in which pro-inflammatory mediators, oxidative stress and NF-kB signaling have a fundamental role. The 1,8-cineole, a monoterpene present in several plants species, is known for its antioxidant and anti-inflammatory potential. In order to verify its efficacy preventing AP, this study evaluated 1,8-cineole (100, 200 and 400 mg/kg, oral) on AP induced by cerulein (50 µg / kg / h × 5, i.p.) in Swiss mice. The 1,8-cineole was administrated one hour before the first injection of cerulein. Groups treated with vehicle or thalidomide were included as controls. Six hours later, blood samples were collected to determine blood levels of amylase, lipase and cytokines. The pancreas was removed for morphological examination, myeloperoxidase (MPO) and malondialdehyde (MDA) trials, changes in reduced glutathione (GSH) and for immunostaining of nuclear factor NF-κB. The right lung was removed for MPO trial. The 1,8-cineole reduced the histological damage and the expression of NF-κB induced by cerulein. Cerulein increased significantly amylase, lipase, TNF- α, IL1- β and IL-6, reducing IL-10. The 1,8-cineole 100, 200 and 400 mg/kg reversed significantly the damages caused by cerulein by reducing amylase (14; 16; 21 %), lipase (49; 48; 42 %), TNF-α (46; 66; 44 %), IL1-β (53; 45 e 67 %) e IL-6 (49; 40; 41 %) and enhanced IL-10 (34; 29 e 46 %), respectively. Cerulein produced pancreatic edema, increased MDA, pancreatic MPO, pulmonary MPO and decreased GSH comparing to the vehicle group (p < 0,05). The 1,8 cineole 100, 200 and 400 mg/kg reduced pancreatic edema (6; 27; 17%), MDA (34; 29; 46%), pancreatic MPO (40; 55 and 78 %), pulmonary MPO (42; 45 and 22 %) and preserved GSH (62; 63 and 65 %). These findings suggest that 1,8-cineol can prevent the severity of cerulein-induced acute pancreatitis in mice through an anti-inflammatory and antioxidant mechanisms.